Improving The Vocabulary Mastery of The Eight Grade Students of SMP Negeri 12 Parepare Through Memory Strategy - Masdalia; Patahuddin (La Parole : Journal of Language Teaching and Pedagogy, 2018)
Vocabulary is basic knowledge of the students to mastery in language skill. Students have a lot of vocabulary automatically able to speak and to write within communication. Limited vocabulary also can influence students’ comprehension in listening and reading. Those become some of the considerations of the researcher to conduct this research when doing an observation at SMP Negeri 12 Parepare since the students show very poor achievement in vocabulary Mastery. In this case, the researcher try to solve the problem of students’ vocabulary mastery by implement one of innovative learning strategies that is Memory Strategy. The objective of the research is to find out whether or not the use of Memory Strategy is able to improve vocabulary mastery of the eighth grade students of SMP Negeri 12 Parepare. The researcher applied quasi-experimental method, with two group pre-test and post-test design. The samples where chosen by using random sampling technique which consisted of 35 students from two classes taken from the population. The result of the data analysis showed that there was significant difference of the students’ vocabulary mastery before and after teaching vocabulary through Memory Strategy. It is proved by the result of the statistical analysis by using SPSS 21.0 application with applying t-test calculation where the significant value of pre-test (0.235) was higher than the level of significant (0.05) and post-test (0.000) was lower than the level of significant (0.05).